'Recognisable Psychiatric Injury' and Tortious Compensability for Pure Mental Harm Claims in NegligenceSaadati v Moorhead [2017] 1 SCR 543(McLachlin CJ and Abella, Moldaver, Karakatsanis, Wagner, Gascon, Côté, Brown and Rowe JJ). Issue 5 (3rd September 2018) - Freckelton, Ian; Popa, Tina
Abstract : Since at least 1970, one of the constraints upon compensability for pure mental harm at common law has been that a plaintiff must have suffered not just adverse psychological consequences from negligence but a 'recognisable psychiatric illness'. In a powerful unanimous decision, the Supreme Court of Canada in Saadati v Moorhead [2017] 1 SCR 543 has controversially removed this requirement. This paper reviews the reasoning in the decision and considers its ramifications, concluding that while it is likely to extend the liability of defendants, this will occur only in a small cross-section of cases where a plaintiff exhibits significant symptomatology of a mental disorder albeit falling short of sufficient for an unequivocal diagnosis within the meaning DSM-5 or ICD-10. It notes that in the post-Ipp reforms in Australia, a 'recognised psychiatric illness' has been statutorily enshrined as a prerequisite to recovery by plaintiffs, so statutory law reform would be required to implement the Saadati decision. While it welcomes the contribution of the Saadati approach to reducing the law's discrimination against mental (as opposed to physical) injuries, it calls for close scrutiny of the actual effects of the Saadati decision.